Influencing factors of nursing informatics competencies and information anxiety in clinical nurses and related coping strategies (临床护士护理信息能力与信息焦虑水平影响因素分析及应对策略) - LUO Qi (罗琦) (Association of Integrative Nursing, 2022)
Objective To investigate the nursing informatics competencies and information anxiety level of clinical nurses, and to explore the correlation and influencing factors of them, so as to provide reference for improving nurses' nursing informatics competencies and relieving nurses' information anxiety. Methods Using stratified random sampling method, 577 clinical nurses from 4 tertiary hospitals in Yunnan Province were selected as the research objects. Questionnaire surveys were carried out using the General Information Questionnaire, the Nurse Information Competencies Scale and the Information Anxiety Scale. Results The score of the Informatics Competencies Scale for Nursing was (121. 01±21. 21), which was at an upper level. The score of Information Anxiety was (3. 13±0. 42), indicating moderate anxiety. Nursing informatics competencies was negatively correlated with information anxiety (ρ=-0. 130, P=0. 002). One-way analysis of variance showed that age, education, information ability training experience were the influencing factors of nursing informatics competencies and information anxiety (P<0. 05). Conclusion Schools and hospitals should pay attention to the needs of nursing informatics competencies improvement, carry out multi-level and diversified training activities, help nurses to effectively solve nursing information problems in work and study, and relieve information anxiety. (目的 调查临床护士护理信息能力与信息焦虑水平, 探讨两者相关性及影响因素, 为提升护士护理信息能力和缓解护士信息焦虑提供参考。方法 采用分层随机抽样法, 选取云南省4所三级甲等医院的577名临床护士为研究对象, 采用一般资料调查表、护士信息能力量表和信息焦虑量表进行问卷调查。结果 护士护理信息能力量表得分为(121. 01±21. 21)分, 处于偏上水平, 信息焦虑得分为(3. 13±0. 42)分, 存在中度焦虑。护理信息能力与信息焦虑呈负相关(ρ=-0. 130, P=0. 002)。护士的年龄、学历、信息能力培训经历是护理信息能力和信息焦虑的影响因素(P＜0. 05)。结论 学校和医院要重视护士护理信息能力提升需求, 开展多层次、多元化的培训活动, 帮助护士解决工作和学习中的护理信息问题, 缓解信息焦虑。)